Decentralized constant-volume control of irrigation canals - Reddy, J. Mohan, author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 1992)
The Saint-Venant equations of open-channel flow were linearized using the Taylor series expansion around an equilibrium condition. A set of linear dynamic equations were obtained for a canal with multiple pools. The principles of optimal control and estimation theory were then applied to derive a decentralized controller and an observer for constant-volume control of irrigation canal pools in the presence of external disturbances acting on the system. using the linearized Saint-Venant equations and an example problem with 5 pools, the performance of the control algorithm in maintaining a constant-volume in the canal pools was found to be excellent.
Irrigation and water resources in the 1990's
Constant-volume control of canals
Not digitized by CSUL Digital Services.
Presented at Irrigation and water resources in the 1990's: proceedings from the 1992 national conference held on October 5-7, 1992 in Phoenix, Arizona.